LEGAL PRINCIPLES OF COMBATING CORRUPTION IN STATE GOVERNMENT BODIES OF UKRAINE (Bulletin of criminological association of Ukraine, 2024)
The article emphasizes that administrative and legal norms in the context of combating corruption play an important role, as they create legal mechanisms to ensure transparency and accountability of state authorities, determine requirements for the declaration of income of officials, control over the use of state resources, as well as administrative liability for violations of anti-corruption norms. Administrative and legal norms not only establish liability for violations of anti-corruption norms, but also regulate organizational and managerial processes aimed at preventing corruption in state authorities. It is argued that in order to increase the effectiveness of administrative and legal norms in combating corruption, it is advisable to implement a number of specific measures. Among other things, it is necessary to improve the mechanisms for monitoring the activities of state authorities, which will allow for more prompt detection of violations and prevention of possible corruption manifestations. It is also necessary to strengthen liability for violations of anti-corruption norms. It is important to ensure greater transparency in the activities of state authorities, in particular by improving mechanisms for public access to information about the activities of officials, the use of state resources and the financing of projects and programs. At the same time, it is necessary to improve the training and advanced training of civil servants on the requirements of anti-corruption legislation and public administration ethics.
Keywords: legal principles; combating corruption; state authorities of Ukraine; anti-corruption policy; problems; administrative and legal norms